To factor the polynomial equation \(2x^5 - 4x^3 + 2x = 0\), we start by factoring out the common terms.
-
Factor out the greatest common factor (GCF): The GCF of the terms \(2x^5\), \(-4x^3\), and \(2x\) is \(2x\). We factor this out:
\[ 2x(x^4 - 2x^2 + 1) = 0 \]
-
Set each factor to zero: Now we can set each factor equal to zero to find the solutions.
From \(2x = 0\): \[ x = 0 \]
Now we solve the quartic equation \(x^4 - 2x^2 + 1 = 0\).
-
Substitute \(y = x^2\): This substitution simplifies \(x^4 - 2x^2 + 1 = 0\) to a quadratic form: \[ y^2 - 2y + 1 = 0 \]
-
Factor the quadratic: The quadratic can be factored as: \[ (y - 1)^2 = 0 \]
Therefore, we have: \[ y - 1 = 0 \implies y = 1 \]
-
Back-substitute for \(x\): Remembering that \(y = x^2\), we have: \[ x^2 = 1 \]
Thus, solving for \(x\) gives us: \[ x = 1 \quad \text{or} \quad x = -1 \]
-
Collect the solutions: Combining all the solutions we found: \[ x = 0, \quad x = 1, \quad x = -1 \]
Therefore, the full set of solutions to the equation \(2x^5 - 4x^3 + 2x = 0\) is: \[ \boxed{0, 1, -1} \]